The Potential Interactive Digital Teaching Material on Cell Metabolism as a Bridge of Cognitive Processes Toward Student Learning Achievement - Cita Tresnawati; Adi Rahmat; Taufik Rahman; Kusnadi Kusnadi (Jurnal Penelitian Pendidikan IPA, 2024)
Education in the era of digital technology has become a challenge for teachers and lecturers in how this technology can develop comprehensive knowledge and global insight. The purpose of this study is to improve learning achievement through the cognitive process of students in cell metabolism lectures using Interactive Digital Teaching Material (IDTM). The study involved 40 Biology Education students who were taking the third semester at one of the Private Universities in Bandung, West Java. The implementation of lectures and instruments to measure students' cognitive processes is based on the framework of the 1992 Marzano Learning Dimension. The results of the analysis showed that the N-gain value of Acquire and Integrate Knowledge and Extend and Refine Knowledge obtained a percentage of (28%-26%) on low criteria. While Using knowledge with a percentage of N-gain value (32%) on medium criteria. These results illustrate that IDTM facilitates students to train their cognitive processes toward better learning achievement